2006
DOI: 10.1149/1.2138679
|View full text |Cite
|
Sign up to set email alerts
|

On the Steady-State Oxygen Permeation Through La[sub 2]NiO[sub 4+δ] Membranes

Abstract: The steady-state oxygen permeation through polycrystalline La 2 NiO 4+␦ , synthesized by a citric acid-based technique and sintered at 1350°C, has been measured as a function of oxygen gradient, temperature ͑850-1000°C͒, and membrane thickness ͑0.3-2.5 mm͒. In agreement with earlier reports, the La 2 NiO 4+␦ membranes show high permeation rates, comparable to those found for the perovskite-related La 1−x Sr x Co 1−y Fe y O 3−␦ materials. The self-diffusion coefficient and the surface exchange coefficient of ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 21 publications
9
54
0
Order By: Relevance
“…The estimated activation energy for · i of Nd 2 NiO 4+¤ is 64-90 kJ mol ¹1 in this study, which is comparable to the reported values of Nd 2 NiO 4+¤ and La 2 NiO 4+¤ . [36][37][38] The result in Fig. 6 shows that oxide ionic conduction governs the oxygen surface exchange coefficient in Nd 2 NiO 4+¤ .…”
Section: Resultsmentioning
confidence: 92%
“…The estimated activation energy for · i of Nd 2 NiO 4+¤ is 64-90 kJ mol ¹1 in this study, which is comparable to the reported values of Nd 2 NiO 4+¤ and La 2 NiO 4+¤ . [36][37][38] The result in Fig. 6 shows that oxide ionic conduction governs the oxygen surface exchange coefficient in Nd 2 NiO 4+¤ .…”
Section: Resultsmentioning
confidence: 92%
“…Thermal efficiencies reported for the AZEP cycle range from 50 [2], to 52.5% [21] for simple, non-optimized flowsheets. However, it should be noted that the AZEP turbine inlet temperature for the efficiencies cited above is 12001C, 2001C above the reported limit for the ITM reactor required for membrane stability [22,23]. The AZEP concept consists of a Brayton cycle combined with a bottoming steam cycle in addition to either an unconventional CO 2 , steam-like turbine, or a heat recovery steam generator that utilizes the availability of the combustion products exiting the ITM reactor [2].…”
Section: Advanced Zero-emission Power Plantmentioning
confidence: 99%
“…Despite its simplifications, this semi-empirical equation well describes the situations where oxygen transport is limited by both surface exchange and bulk ionic conduction, as typical for La 2 NiO 4 -based materials [42,43].…”
Section: Appendixmentioning
confidence: 99%
“…The membrane material considered in the present work is intergrowth lanthanum-nickel oxide (La 2 NiO 4+δ ) [39][40][41][42][43] with K 2 NiF 4 -type structure. This composition and its derivatives exhibit a series of important advantages, namely quite high oxygen permeability, moderate thermal expansion compatible with glass-ceramic sealants and stainless steel, very low chemical-induced stresses and absence of alkaline-earth cations that may promote interaction with gaseous species such as CO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation